2006
DOI: 10.1093/ije/dyl049
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen and lung function: the CARDIA Study

Abstract: These findings are consistent with the hypothesis that fibrinogen, possibly as a marker for chronic low-grade inflammation, is associated with modest deterioration of lung function in healthy young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 34 publications
8
79
1
7
Order By: Relevance
“…In accordance with the present findings, SHAABAN et al [13] found an association between CRP at baseline and a decline in FEV1 in middle-aged subjects (average age 37 yrs) over a follow-up period of 8.5 yrs, although this association did not reach formal significance (p50.07). Additionally, plasma fibrinogen, another marker of systemic inflammation, was found to predict subsequent lung function decline in a 5-yr follow-up study of young American adults [12]. This indicates that different markers of systemic inflammation may be similar in predicting changes in lung function.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In accordance with the present findings, SHAABAN et al [13] found an association between CRP at baseline and a decline in FEV1 in middle-aged subjects (average age 37 yrs) over a follow-up period of 8.5 yrs, although this association did not reach formal significance (p50.07). Additionally, plasma fibrinogen, another marker of systemic inflammation, was found to predict subsequent lung function decline in a 5-yr follow-up study of young American adults [12]. This indicates that different markers of systemic inflammation may be similar in predicting changes in lung function.…”
Section: Discussionmentioning
confidence: 85%
“…The temporal relationship between systemic inflammation and poor lung function is also unclear. Although several studies have explored this association [1,[10][11][12][13][14][15], each of these studies had certain limitations. Some of these studies were cross sectional in nature and unable to assess the temporal relationships [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both diseases have been related to systemic inflammation [16][17][18][19][20]. Individuals with airflow limitation demonstrate airway and systemic inflammation, depending on the severity of lung disease, physical fitness and potential comorbidities [17][18][19]. Besides smoking [21] and obesity [22], risk factors for lung function decline and airflow limitation are ageing and pulmonary diseases, such as chronic obstructive pulmonary disease (COPD) [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, fibrin is also detected along the luminal surface of distal airways in patients dying from asthma (Wagers et al 2004). Inverse association exists between lung function and blood levels of fibrinogen (Thyagarajan et al 2006, Huang et al 2012. Although the effect of fibrin on ASM is undefined, mice lacking fibrinogen demonstrate an attenuated AHR in the context of allergic airway inflammation (Riesenfeld et al 2012).…”
Section: Blood-derived Factorsmentioning
confidence: 99%